Drought elicits contrasting responses on the autumn dynamics of wood formation in late successional deciduous tree species. (22nd February 2021) - Dox, Inge; Prislan, Peter; Gričar, Jožica; Mariën, Bertold; Delpierre, Nicolas; Flores, Omar; Leys, Sebastien; Rathgeber, Cyrille B K; Fonti, Patrick; Campioli, Matteo
Abstract: Research on wood phenology has mainly focused on reactivation of the cambium in spring. In this study we investigated if summer drought advances cessation of wood formation and if it has any influence on wood structure in late successional forest trees of the temperate zone. The end of xylogenesis was monitored between August and November in stands of European beech and pedunculate oak in Belgium for two consecutive years, 2017 and 2018, with the latter year having experienced an exceptional summer drought. Wood formation in oak was affected by the drought, with oak trees ceasing cambial activity and wood maturation about 3 weeks earlier in 2018 compared with 2017. Beech ceased wood formation before oak, but its wood phenology did not differ between years. Furthermore, between the 2 years, no significant difference was found in ring width, percentage of mature fibers in the late season, vessel size and density. In 2018, beech did show thinner fiber walls, whereas oak showed thicker walls. In this paper, we showed that summer drought can have an important impact on late season wood phenology xylem development. This will help to better understand forest ecosystems and improve forest models.